2016
DOI: 10.1063/1.4952614
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacity measurements of sub-nanoliter volumes of liquids using bimaterial microchannel cantilevers

Abstract: Lab-on-a-Chip compatible techniques for thermal characterization of miniaturized volumes of liquid analytes are necessary in applications such as protein blotting, DNA melting, and drug development, where samples are either rare or volume-limited. We developed a closed-chamber calorimeter based on a bimaterial microchannel cantilever (BMC) for sub-nanoliter level thermal analysis. When the liquid-filled BMC is irradiated with infrared (IR) light at a specific wavelength, the IR absorption by the liquid analyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…40,41 In particular, photothermal nanomechanical IR sensing (NAM-IR) has been developed for both deflection and resonance frequency detection schemes. 32,33,4249…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 In particular, photothermal nanomechanical IR sensing (NAM-IR) has been developed for both deflection and resonance frequency detection schemes. 32,33,4249…”
Section: Introductionmentioning
confidence: 99%
“…In the last 15 years, nanomechanical sensing has been exploited for biosensing purposes and material characterization. , In particular, photothermal nanomechanical IR sensing (NAM-IR) has been developed for both deflection and resonance frequency detection schemes. ,, …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, suspended microchannel resonators (SMR) have been demonstrated to be excellent tools for highly sensitive detection of both colloidal particles (measuring its buoyant mass) [ 14 , 15 , 16 , 17 ] and liquid properties (by measuring its mass density, viscosity, etc.) [ 18 , 19 , 20 , 21 , 22 ]. Among other nanomechanical techniques, SMR approach is characterized for placing a liquid inside the resonator while vibrating in vacuum or gaseous atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, a BMC undergoes a mechanical deflection in response to the heat produced by the IR radiation. Khan et al demonstrated the use of a BMC as a closed-chamber calorimeter that is optically heated with IR radiation to successfully measure the heat capacity of five volatile organic compounds (VOCs) with varying thermal outputs [37]. The reported system was able to provide online thermal characterization of small volumes of liquids with a resolution of 23 mJ/(gK).…”
Section: Introductionmentioning
confidence: 99%